2009
DOI: 10.1097/hcr.0b013e3181b4c8bd
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Improve Cardiopulmonary Fitness in Cardiac Rehabilitation

Abstract: Twenty-one percent of CR participants failed to improve peakV(O(2)) primarily due to exercise training performed at lower relative intensity despite a similar rating of perceived exertion. For patients with baseline characteristics associated with nonimprovement, alternative training protocols should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 42 publications
4
66
1
Order By: Relevance
“…In previous reports of CABG patients, age was not correlated with change in peak VO 2 11 . In the current study, the valve patients were significantly older than individuals in the CABG group.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In previous reports of CABG patients, age was not correlated with change in peak VO 2 11 . In the current study, the valve patients were significantly older than individuals in the CABG group.…”
Section: Discussionmentioning
confidence: 59%
“…For individuals with coronary heart disease, it has been previously shown that a diagnosis of T2DM is associated with lesser improvements in peak VO 2 11, 23 . Similarly, our results indicate that T2DM and HbA1c are negatively associated with changes in aerobic fitness for individuals rehabilitating from valve-related surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…101,102 Although this might suggest that patients with coexistent heart and lung disease would be particularly benefited by exercise rehabilitation, some data suggest that the presence and burden of comorbid conditions are predictive of ineffectiveness of exercise rehabilitation interventions. 99,103 Given the frequency of coexistent heart and lung disease and the implications this has for functional prognosis, there is remarkably little reported specifically about exercise responses in patients with mixed disease. 104 There is clearly a need to better define the interactive effects of coexistent heart and lung diseases on functional capacity and the most effective approaches to these patients in the rehabilitation setting.…”
Section: Arena and Sietsema Cpx In Clinical Practicementioning
confidence: 99%
“…The study authored by Savage et al, which included 385 patients in CR program, showed that 81 (21%) patients failed to improve peak VO 2 after termination of the program. 13 Similarly, patients with peak VO 2 bellow 10ml/kg/min had a poor prognosis, and those above 18ml/kg/min had a good prognosis.…”
mentioning
confidence: 99%